1994
DOI: 10.1017/s0003356100007042
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of birth and weaning weight of Gudali and two-breed synthetic Wakwa beef cattle populations under selection in Cameroon: genetic and phenotypic trends

Abstract: Breeding programmes for Wakwa and Ngaundere Gudali cattle breeds were initiated in Wakwa (Cameroon) in 1952 and 1965, respectively, to improve growth performance of the indigenous breeds. Animals were selected on 240-day weaning weight (WWT). Data analysed covered the period 1971 through 1985 and consisted of 2211 calf birth weight (BWT) and 1409 WWT records on Gudali and 1196 BWT and 763 WWT records on Wakwa. Selection responses in BWT and WWT were estimated as regressions of average sire estimated transmitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
7
1
1
Order By: Relevance
“…A longer GI than that found in this study was reported for Gir cattle (8.02 years) in Brazil (Q ueiroz and L ôbo 1993) and for Wakwa cattle (8.67 years) in Cameroon (T awah et al 1994). However, this is still relatively long when compared with the overall average of 4.36 years (M rode 1988) from several beef cattle selection experiments, though this is largely from temperate breeds.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…A longer GI than that found in this study was reported for Gir cattle (8.02 years) in Brazil (Q ueiroz and L ôbo 1993) and for Wakwa cattle (8.67 years) in Cameroon (T awah et al 1994). However, this is still relatively long when compared with the overall average of 4.36 years (M rode 1988) from several beef cattle selection experiments, though this is largely from temperate breeds.…”
Section: Resultscontrasting
confidence: 57%
“…In both reports, a higher level of gain was reported in a single generation of selection than in the present study. T awah et al (1994) also reported annual changes in the sire‐estimated transmitting ability of 0.67 and 1.69 kg per year for WW in Gudali (African zebu) and Wakwa (a synthetic breed between Gudali and Brahman), respectively, in Cameroon.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Results from IRAD Wakwa Centre (Fig. 3) show how during a 17 year period selection (conventional genetic modification) modified the genetic structure of Gudali beef cattle population (Ebangi et al, 2002) with long generation intervals (7-8 years) (Tawah et al, 1994). The target trait was growth (increased beef production).…”
Section: Migration (Introgression)mentioning
confidence: 99%
“…Héritabilités et corrélations génétiques directes et maternelles des performances de croissance chez le Goudali et le Wakwa Pn: Poids à la naissance, GMQ: Gain moyen quotidien, PS: Poids au sevrage, Pa: Poids annuel, P 18 : Poids à 18 mois, h A : Héritabilité directe, h M : Héritabilité maternelle, h T : Héritabilité totale, C 2 : Variance permanente environnementale maternelle, C AM : Covariance maternelle directe, r AM : Corrélation génétique entre les effets génétiques et maternels Ebangi et al (2001)obtenu durant la période de l'expérience est de 8,60 kg et 20,40 kg, respectivement, chez le zébu Goudali (variété Ngaoundéré) et la race synthétique Wakwa(Tawah et al, 1994). Cependant, les corrélations génétiques négatives entre les effets directs et maternels montrent que le progrès génétique serait davantage plus important si la sélection était concentrée sur les performances directes et maternelles(Tawah et al, 1994 ;Ebangi et al, 2001).Lhoste (1975) (%) : Pourcentage de réussite de l'insémination artificielle Lhoste (1975) estime que les faibles taux de réussite de l'insémination artificielle du Tableau 8 sont liés aux avaries subies par les semences. Il précise que la première avarie intervenue en 1969 était dûe à une déficience du récipient cryogénique, et la deuxième dûe à la détérioration du récipient destiné au transport d'azote.…”
unclassified